Ischemia-reperfusion injury in kidney transplantation from non-heart-beating donor--do antioxidants or antiinflammatory drugs play any role? - Treska, V; Kobr, J; Hasman, D; Racek, J; Trefil, L; Reischig, T; Hes, O; Kuntscher, V; Molacek, J; Treska, I (Bratislavske lekarske listy, 2009)
BACKGROUND: Ischemia reperfusion injury (IRI) is a serious problem of transplanted kidneys from a non-heart-beating donor (NHBD). IRI is probably the main cause of primary disfunction or delayed graft function. The aim of this study was to demonstrate the reduction of IRI by intravenous application of antioxidants or immunosuppressives to the recipient before the kidney transplantation in an experimental model. METHOD: Piglets weighing between 20-25 kg were used (n=45) for the experiment. Intravenous application of multivitamins (GI) and a combination of immunosuppressives (GII) was tested one hour before the kidney transplantation from the NHBD. In control group (GIII) simple NHBD modelling was used. Plasma levels of malondiadehyde (MDA) and reduced glutathione (GSH) were assessed at intervals of 0, 20, 60 and 120 minutes after the kidney transplantation. Concentrations of both MDA and GSH were also assessed in the transplanted kidney before and 120 minutes after transplantation. RESULTS: A permanent increase in MDA plasma concentrations occurred in GIII. In GI and GII, after a transient increase in MDA plasma levels within the first 20 minutes after reperfusion, it decreased permanently (p<0.05, p<0.01). MDA plasma levels were not significantly different between GI and GII groups, but both groups differed from GIII (p<0.001). GSH plasma levels and tissue concentrations of MDA and GSH were not statistically significant in any group in the course of the experiment. CONCLUSION: Intravenous application of multivitamins or immunosuppressives before kidney transplantation could have a significant influence on the immediate function of transplanted kidneys from a NHBD (Tab. 3, Fig. 1, Ref. 13). Full Text (Free, PDF) www.bmj.sk.
Keywords: Vitamins; Immunosuppressive Agents; Malondialdehyde; Antioxidants; malondialdehyd; antiflogistika; transplantace ledvin; Mycophenolic Acid; Glutathione; reperfuzní poškození; mužské pohlaví; kyselina mykofenolová; Infusions, Intravenous; Reperfusion Injury; intravenózní infuze; Sus scrofa; hydrokortison; antioxidancia; Hydrocortisone; Kidney Transplantation; zvířata; imunosupresiva; vitaminy; Anti-Inflammatory Agents; glutathion; Male; Animals